Dual-view ice crushing experiments - Daley, C.; Gagnon, R. E. (National Research Council of Canada. Institute for Ocean Technology, 2006)
Ice is a unique and fascinating material. Much like the rock of the earth's crust, sea ice can form a crust on the cold oceans of the world. The eastern coastal waters in Canada are prone to extensive ice coverage. Ice will often be the dominant consideration in the design of ships and offshore structures in Canadian waters. There are many Polar and sub-Polar areas of the world where sea ice is also the dominant natural feature and the key design challenge. Consequently, improving our understanding of ice loads is a topic of large practical significance, as well as being a fascinating scientific challenge. Several studies of ice crushing behavior have been conducted over of the past few decades. Some of the more recent investigations included in situ visual observations using indentors (Joensuu and Riska, 1988, Muhonen 1991, Gagnon, 1998; Fransson et al., 1991, Daley 1994) and a ship hull (Riska et al., 1990) that incorporated windows for viewing the indented ice surface. There have also been test apparatus that allowed viewing of the ice/indentor interface through the ice samples (Gagnon, 1994a; Gagnon and Mølgaard, 1991). These have lead to significant new insights into the ice crushing process. Numerical contact process models based on available visual observations have been developed (Daley 1991, Daley et al. 1996). Further developments of these models is one of the continuing aims of this experimental work. The present study incorporates a similar concept to that of Wilson (1999), except that the strain rate is much higher, and is in the range associated with ice crushing rather than plastic deformation. The loads are much higher and the apparatus is correspondingly stronger. Experiments similar to the present ones have been performed by Gagnon (2004). While much progress has been made in the last 2 decades concerning the processes involved in ice crushing, considerable study remains in order to resolve divergent views that have developed. The importance of observing the ice behavior is, no doubt, a key ...